1998
DOI: 10.1139/f98-113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat isolation on the recovery of fish assemblages in experimentally defaunated stream pools in Arkansas

Abstract: We removed fish from pools in two Arkansas streams to determine recolonization rates and the effects of isolation (i.e., riffle length, riffle depth, distance to large source pools, and location), pool area, and assemblage size on recovery. To determine pool-specific recovery rates, we repeatedly snorkeled 12 pools over a 40-day recovery period. Results indicated the effects of isolation on percent numerical recovery, but no effects of pool area or assemblage size. Numerical recovery of assemblages in pools se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 20 publications
6
62
1
3
Order By: Relevance
“…We have shown previously that population estimates generated from snorkeling surveys in these streams are nearly identical to those generated from more invasive and laborintensive electrofishing surveys (Lonzarich et al 1998). High water clarity provided excellent conditions for identifying marked fish from distances up to 3 m.…”
Section: Experimental Designmentioning
confidence: 71%
See 2 more Smart Citations
“…We have shown previously that population estimates generated from snorkeling surveys in these streams are nearly identical to those generated from more invasive and laborintensive electrofishing surveys (Lonzarich et al 1998). High water clarity provided excellent conditions for identifying marked fish from distances up to 3 m.…”
Section: Experimental Designmentioning
confidence: 71%
“…General characteristics of the streams included bedrock and gravel substrates and dense riparian vegetation. The proportion and average size of pool and riffle habitats in the two streams were similar (Clingenpeel 1994) as were the composition, rank dominance, and densities of fish species (Lonzarich et al 1998). Physical and biological conditions during the two years of the study also were very similar.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Less than 20% of the slimy sculpin migrated, and 80% of those moved less than 25 m. Natsumeda (1999) found that the mean movements of the male and female Japanese fluvial sculpin Cottus pollux was less than 20 m. Petty and Grossman (2004) found that most individual mottled sculpin moved less than 3 m. The longest movement of slimy sculpin and a second, undescribed sculpin species documented by Schmetterling and Adams (2004) was 209 m. Greater distances may have been observed if traps had not obstructed movement. Some stream fishes can be highly mobile, and recolonization by some fish assemblages can occur on the scale of days or weeks (Peterson and Bayley 1993;Lonzarich et al 1998, …”
mentioning
confidence: 99%
“…Estos Ășltimos son menos extensivos y no sincrĂłnicos (Albanesse et al 2004), pero son igualmente de gran signifi cado ecolĂłgico. Tales movimientos locales permiten colonizar nuevos hĂĄbitats (Taylor 1997;Lonzarich et al 1998), o moverse entre microhĂĄbitats, generando una alta dinĂĄmica espacial y temporal de las poblaciones en un sistema fl uvial (Schlosser & Angermeier 1995). Estos movimientos pueden estar gatillados por factores endĂłgenos (e.g.…”
Section: Introductionunclassified